Raising Arizona's Dams : Daily Life, Danger, and Discrimination in the Dam Construction Camps of Central Arizona, 1890s-1940s - Rogge, A. E. (Book collections on Project MUSE., 1995)
This is the engrossing story of the unsung heroes who did the day-to-day work of building Arizona's dams, focusing on the lives of laborers and their families who created temporary construction communities during the building of seven major dams in central Arizona. The book focuses primarily on the 1903-1911 Roosevelt Dam camps and the 1926-1927 Camp Pleasant at Waddell Dam, although other camps dating from the 1890s through the 1940s are discussed as well. The book is liberally illustrated with historic photographs of the camps and the people who occupied them while building the dams.